Medical Image Encryption by Using Modification of SomdipDey Advanced Encryption Image Technique - Al Farissi; Agung Wahyu Nugroho; Megah Mulya (IAES Indonesia Section, 2014)
The rapid growth of technology led the security ofdata becomes a very important issue, in particular data onmedical field. Therefore the security of data need to beconsidered. This research will focus on the security of medicalimage. The appropriate technologies to increase the security ofmedical image is the image encryption. This research, applied atechnique that can encrypt a medical image, it is SompdipDeyAdvanced Encryption Image Technique. This technique hasthree phases, namely Bits Rotation and Reversal, Extended HillCipher and Modified MSA Randomization. This research wasalso conducted on a modification of the stage Extended HillCipher that produces a better result so that the security ofmedical data will be increased.